1957
DOI: 10.1149/1.2428515
|View full text |Cite
|
Sign up to set email alerts
|

Thermogalvanic Potentials and Currents at Aluminum Surfaces in Industrial Water

Abstract: normal until it began to fluctuate at @. Although this fluctuation was found on two of the four cells in this cycle, it is not characteristic of a normal charge. Lacking any other information, this erratic behavior might be confused with a bad electrical connection or breakdown of measuring component. A similar fluctuation ~ppears at Q on cell 2, but, from the additional data taken, it is obvious that the fluctuations in the cell voltage are due to fluctuations in the negative plate potential @, and are also r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1965
1965
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…the formation of a passive film on the anode surface), so it is not suitable. Thus, in practice, any enhanced corrosion as a consequence of the apparition of a temperature gradient between different zones of the same metal is regarded as thermogalvanic corrosion [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the formation of a passive film on the anode surface), so it is not suitable. Thus, in practice, any enhanced corrosion as a consequence of the apparition of a temperature gradient between different zones of the same metal is regarded as thermogalvanic corrosion [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of thermal gradients in contributing to corrosion of industrial equipment has been reported in numerous studies [17,[23][24][25][26][27][28][29][30]. Thermogalvanic corrosion resulting from temperature gradients can cause the early failure of copper pipes exposed to a sustained temperature gradient.…”
Section: Introductionmentioning
confidence: 99%